Medieval Floor Tiles of Northern England Pattern and purpose: production between the 13th and 16th centuries - Stopford, Jennie (Historic England, 2005)
This study of the design, manufacture and use of medieval floor tiles shows the long-lasting influence achieved in the north of England, especially by the Cistercian monasteries. It serves to demonstrate how these monastic houses made use of the resources and contacts available to them. The study focuses on one of the richest medieval floor tile assemblages in the world, with material from 118 sites. Over 500 different designs and 60 mosaic arrangements have been identified. Jennie Stopford examines the monastic influence on northern England's manufacture and use of floor tiles. Split into three sections - Chronological Survey, The Tile Groups, and The Sites and Collections - this in-depth study covers an immense body of work.